Experimental Study of Digitizers Used in High-Precision Impedance Measurements - Krzysztof Musioł (Energies, 2022)
In the currently used primary impedance measuring systems, there is a need to compare standards with ratios different from 1:1, e.g., in order to transfer the value to multiples or submultiples of the basic quantity. Unfortunately, the commercial PXI sampling systems used to measure the voltage ratio in the impedance bridge, although they provide adequate resolution, show a considerable non-linearity of the measurement. This leads to significant error of the impedance ratio measurement. Experimental studies of commercial PXI digitizers used in primary impedance metrology are presented in the paper. The scope of the work includes presentation of the sampling measurement system hardware used in electronic synchronous impedance bridges and studies of the parameters that affect the applicability of PXI digitizers in high-precision measuring instruments. Nonlinearity errors of digitizers on boards NI PXI-4461 and NI PXI-4462 were measured and appropriate conclusions regarding possible corrections of the errors were drawn.